Through a maze of studies: health questions and 'undone science' in a French industrial region. Issue 2 (3rd April 2017) - Allen, Barbara L.; Ferrier, Yolaine; Cohen, Alison K.
Abstract : Near the city of Marseille is one of France's largest industrial regions, home to over 400 industrial facilities. Adjacent to these facilities are towns whose residents have complained of myriad health problems, from respiratory illness and autoimmune disease to cancers. While human environmental health in this region has been studied repeatedly by state agencies and allied organizations, the studies focused on tightly constructed questions answerable within particular languages of expertise. This rarely translated into information that residents found relevant or credible in relationship to their own experience living in their polluted communities. We argue that these disciplinarily circumscribed health studies are conditioned by the way policy-relevant science is produced in France given the strong centralized state and its civil service elite. Thus many residents' questions remain unanswered and the absence of answers produce a form of ignorance called 'undone science'. We examine three studies paradigmatic of the kinds of health research that has been done in the region. We illustrate the disconnect between the profession-driven studies' questions and outcomes, and the areas of greatest interest to residents. In concluding, we advocate for study designs which engage with local residents and attempt to fill the knowledge gap of their unanswered questions.